2003
DOI: 10.1523/jneurosci.23-21-07767.2003
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide Increases after Focal Cerebral Ischemia and Potentiates Microglial Cell Motility

Abstract: Focal cerebral ischemia (FCI) induces rapid neuronal death in the ischemic core, which gradually expands toward the penumbra, partly as the result of a neuroinflammatory response. It is known that propagation of neuroinflammation involves microglial cells, the resident macrophages of the brain, which are highly motile when activated by specific signals. However, the signals that increase microglial cell motility in response to FCI remain mostly elusive. Here, we tested the hypothesis that endocannabinoids medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
159
2
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 219 publications
(165 citation statements)
references
References 72 publications
3
159
2
1
Order By: Relevance
“…In 1993, two other N-AEs, N-homo-γ-linolenoylethanolamine (HEA) and Ndocosatetraenoylethanolamine (DEA), were found in brain, and shown to activate CB 1 receptors with nanomolar affinity [19;20]. Our laboratory confirmed the presence of both these N-AEs in intact brain and showed that focal cerebral ischemia leads to their accumulation in the diseased tissue [21]. Our laboratory also showed that HEA and DEA are produced in an activity-dependent manner by neurons, astrocytes and microglial cells in culture, and that they stimulate microglial cell migration [11;12].…”
Section: Introductionmentioning
confidence: 69%
“…In 1993, two other N-AEs, N-homo-γ-linolenoylethanolamine (HEA) and Ndocosatetraenoylethanolamine (DEA), were found in brain, and shown to activate CB 1 receptors with nanomolar affinity [19;20]. Our laboratory confirmed the presence of both these N-AEs in intact brain and showed that focal cerebral ischemia leads to their accumulation in the diseased tissue [21]. Our laboratory also showed that HEA and DEA are produced in an activity-dependent manner by neurons, astrocytes and microglial cells in culture, and that they stimulate microglial cell migration [11;12].…”
Section: Introductionmentioning
confidence: 69%
“…While PEA is found in significant levels in whole mouse or rat brains (100-550 pmol/g) Fegley et al 2004;Franklin et al 2003;Patel et al 2005), pathophysiological stimuli may selectively increase its levels. Neurons in culture produce PEA (Stella and Piomelli 2001) and astrocytes produce 2 to 3 times more PEA than AEA (Walter et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…They both are present in the CNS and peripheral tissues, with PEA often being ten times more abundant than AEA (Cadas et al 1997;Calignano et al 1998;Franklin et al 2003). Specific stimuli may lead to their independent accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…There are notable studies showing the anti-inflammatory properties of cannabinoid-like compounds, such as D 9 -tetrahydrocannabinol (THC) metabolites and the endogenous compound palmitoylethanolamide. Since these compounds do not act through known cannabinoid receptors (Dajani et al, 1999;Lambert et al, 1999;Franklin et al, 2003;Zurier et al, 2003), we will only discuss them briefly here.…”
Section: Introductionmentioning
confidence: 99%